Fostering Science Literacy in Indonesia and its Impact: A Systematic Literature Review - Listiawan, Listiawan; Winarto, Winarto; Wilujeng, Insih; Rahmawati, Laifa; Faisal, Nur Zamzam Yuniar; Dewanto, Riski (Proceeding International Conference on Religion, Science and Education, 2026)
Science literacy remains a central issue in education, encompassing not only conceptual understanding but also awareness of scientific processes, socio-scientific issues, and empirical reasoning. This study conducted a systematic literature review using the PRISMA protocol, covering identification, screening, eligibility, and inclusion. A total of 20 international articles indexed by Scopus and accredited by Sinta 1 or 2 were analyzed. The findings show that approaches such as STEM, project-based learning, interactive e-modules, and environment-based activities significantly improve science literacy. Instructional models like MURDER, IB-NOSA, JAS with Google Lens, and graphic organizers also have positive impacts. Moreover, digital tools—including flipbooks, virtual-reality games, and culturally contextual modules—further enhance comprehension. Assessment instruments such as SLiSIS and Lisa3D exhibit strong validity in measuring science literacy. These findings highlight the importance of integrating technology and contextual strategies to effectively foster students’ scientific literacy.